Dependent Plurality and the Theory of Scalar Implicatures: Remarks on Zweig 2009. (25th May 2020) - Ivlieva, Natalia
Abstract: Following a recent discussion in Fox & Spector 2018, this paper provides an argument for a particular view of the theory of scalar implicatures and exhaustification where exhaustification is only allowed if it alters the overall sentence meaning without weakening it. I show that this idea is helpful to make sense of the so-called dependent plural interpretations, addressed within the theory of scalar implicatures in Zweig 2009 (see also Zweig 2008 ). Even though Zweig's account is based on insightful and plausible assumptions (most crucially, the idea that the multiplicity component of the meaning of plurals is a scalar implicature), it ultimately fails to derive dependent plural readings. The main reason for this is the use of the Strongest Candidate Principle of Chierchia 2006 that happens to filter out the needed interpretation. Replacing the Strongest Candidate Principle with a weaker constraint on exhaustification along the lines of Fox & Spector 2018 resolves the issue, while keeping most of Zweig's insights intact.